Renewal of sp2 bonds in graphene oxides via dehydrobromination - Chua, Chun Kiang (2013)
Graphene-based materials are emerging to become one of the most exciting candidates for various applications. There has been a keen interest in developing methods that will not only result in their bulk production, but could also generate graphene-based materials that possess good electrical and physical properties. The most convenient method towards bulk production of graphene-based materials is often via the reduction of graphene oxide. In this context, numerous reduction techniques have been previously applied based on standard organic chemistry reagents. Although most standard reducing agents work well in the removal of oxygen-containing groups from the graphene oxide surfaces, they do not theoretically result in the important restoration of the defective sp2 carbon network. Particularly in this work, we focused on the restoration of the defective sp2 carbon network of graphene oxide via a dehydrohalogenation method. This was achieved through a prior substitution of hydroxyl to bromine groups, followed by a dehydrobromination step. This strategy offers a great potential for the production of chemically reduced graphene of high conductivity.